Evaluación de metales pesados bioacumulables en peces provenientes de quebradas ubicadas en el Lote 192 del Río Corrientes - Ramirez Chávez, Jemima Cesia (2024)
The present study was carried out in the upper and lower basin of the Corrientes River, Loreto region, Peru; in streams located between the native communities Antioquia and Jose Olaya, adjacent to Lot 192, in the month of September 2016 and in streams located near the town center of Trompeteros in the month of June 2018 times of river flooding. The objective was to evaluate the concentrations of bioaccumulative heavy metals in fish from streams located in lot 192 of the Corrientes River. The method of collecting fish was used through the use of fishing gear such as gill nets, and then processing the muscles of the fish collected using the atomic absorption spectrophotometry (AEE) method to determine the concentrations of metals, lead. (Pb), cadmium (Cd) and copper (Cu), the resulto f which was compared with the maximum permissible limits for fish or fishery products for human consumption. In total, 55 individuals belonging to 13 species of fish were captured. The bioaccumulation of Pb and Cd in the muscle tissue of the 55 fish was lower than the quantification limit of the method (< 3 mg of Pb/kg and < 0.2 mg of Cd/kg); while the metal copper (Cu) recorded values of 1.7 to 3.4 mg/Kg in omnivorous fish (n= 29), 1.7 to 3.1 in piscivorous fish (n=23) and 3.3 to 3.9 in detritivores (n=3). Likewise, the concentrations of the metal copper in the muscle tissue of the fish were below the Maximum Permissible Limits by national and international standards. The fish analyzed from the Corrientes River can be consumed by residents.